Интеллектуальная революция 21 века в системе высшего образования - Бравый, К. Л. (Eastern-European Journal of Enterprise Technologies, 2009)
In the article a new epoch is presented in development of sciences, intellectual technologies, higher education and spiritual culture of postindustrial’noy civilization. ”Intellectual revolution of 21th age in the system of higher education” is component part of ”INLIGHTENING in 21-ohm eyelid”, which on principle differs from ”INLIGHTENING in 18-ohm age” in that it is directed on mastering of sciences, intellectual technologies, higher education and spiritual culture of postindustrial’noy civilizatio